Acknowledgement - Batkhishig, Bayaraa; Altanzul, Baasandorj; Munkhtsengel, Baatar; Tseedulam, Khuut (Mongolian Geoscientist, 2021)
We sincerely thank to the journal Editors and Invited Reviewers of our open access volumes No 50, 51 and 52. They are the people who make an internationally peer reviewed, open access journal. Reviewer’s helpful and constructive comments led to improvement in each manuscript and successful volumes.